Escola de tempo integral: uma an??lise da experi??ncia do programa mais educa????o nas escolas do munic??pio de Barueri - Carvalho J??nior, Raimundo Nonato de (2016)
In 2013, the Municipal Secretary of Education of Barueri announced that 4 schools from its school system joined the federal government educational program Mais Educa????o. This research aims to understand these schools teachers concept of integral education. Our central inquiry can be broken down into two questions: how teachers understand the objectives, procedures, concepts and guidelines of Mais Educa????o Program and what changes occurred (or not) in the pedagogical work of these teachers. Primary research sources were constituted of the official documents that support the Mais Educa????o Program and 5 questionnaires answered by full-time schools teachers in the city of Barueri. The purpose of the questionnaires was to obtain data on teachers??? training, their understanding of comprehensive education and their analysis of the educational work process after joining the Mais Educa????o Program. In the face of the findings in this research, it is possible to state that there is little understanding of the debate on comprehensive education among teachers; they do not observe significant changes in educational work related to joining Mais Educa????o Program; and that full-time schools in Barueri are seen as children and adolescents occupancy and restraining environments. Those spaces are no longer educational, they became only of protection and guard and compensation for the exclusion suffered by the working class.